Role of priming technique on germination parameters of calendula (Calendula officinalis L.) seeds - Karimi, Mahnaz; Heidarzade, Ayoub; Varyani, Masomeh (Journal of Agricultural Sciences (Belgrade), 2016)
Priming is one of the seed enhancement methods that might be resulted in increasing seed and seedling properties under stress conditions such as salinity, temperature and drought stress. Poor plant stand establishment is a common problem for marigold production. Therefore, an experiment was conducted to investigate germination characteristics and enzyme activity of calendula seeds. For this purpose, different seed priming techniques: hydroprimng (Distilled water, 24 and 72 h ), osmopriming (0.02% or 0.04% KNO3 for 24 and 72 h) and hormonal priming (100 or 500 mg L-1 GA3 for 24 and 72 h) were assessed. Seeds without any treatment were considered as control. 100 mg L-1 GA3 and distilled water for 72 h were the most effective treatments in enhancing germination percentage. The highest and lowest vigor indices estimated as 525.75 and 311.50 related to hydro-priming (for 24) and control treatments, respectively. Interaction between priming treatment and time duration on root length was significant. Highest means of root length was found with 0.02% KNO3 for 72 h. Catalase significantly increased in the primed seeds. The highest CAT activity and total soluble sugar were found in the seeds primed with 100 mg L-1 GA3 for 72 h. Moreover, the enzyme activity was significantly higher in the distilled water and KNO3 treatments compared with the untreated seeds.